2008
DOI: 10.1007/s00595-007-3747-6
|View full text |Cite
|
Sign up to set email alerts
|

Solitary splenic metastasis of ovarian carcinoma: Report of two cases

Abstract: Capsular splenic metastasis from ovarian cancer, which is associated with peritoneal spread, is not uncommon. Conversely, solitary involvement of the splenic parenchymal is unusual, and secondary debulking may improve the prognosis if there is no sign of residual disease. Thus, splenectomy is indicated for this type of isolated splenic metastasis. We report two cases of successful splenectomy for solitary splenic metastasis of ovarian carcinoma and review the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Among isolated splenic metastasis, isolated splenic parenchymal lesions are more infrequent and represent the hematogenous spreading of the malignancy. 10,17,18 Chen et al, 20 in 2000, evaluated the role of splenectomy at the time of surgical cytoreduction in advanced ovarian cancer and concluded that it could be performed with acceptable morbidity. More authors in more recent years suggest to incorporate upper abdominal resection in advanced ovarian cancer to achieve a complete cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…Among isolated splenic metastasis, isolated splenic parenchymal lesions are more infrequent and represent the hematogenous spreading of the malignancy. 10,17,18 Chen et al, 20 in 2000, evaluated the role of splenectomy at the time of surgical cytoreduction in advanced ovarian cancer and concluded that it could be performed with acceptable morbidity. More authors in more recent years suggest to incorporate upper abdominal resection in advanced ovarian cancer to achieve a complete cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of ovarian clear cell carcinoma (OCCA) is relatively infrequent, accounting for 5% of all ovarian malignancies and 3.7–12.1% of all epithelial ovarian carcinomas (5–7). As reported previously, OCCA has a distinct histological type with poor prognosis and resistance to platinum-based chemotherapy (7,14). The majority of patients with advanced or recurrent OCCA have a low benefit-to-failure ratio from palliative chemotherapy (7).…”
Section: Introductionmentioning
confidence: 60%
“…Most cases of solitary splenic metastasis documented in the literature were diagnosed with stage III disease (FIGO classification), and underwent optimal tumor debulking [10]. The histological finding of the case described here was high-grade carcinoma consistent with metastatic endometrioid-type ovarian carcinoma, grade 3, stage 1A (FIGO classification).…”
Section: Discussionmentioning
confidence: 88%